PEMBELAJARAN MATEMATIKA DENGAN MODEL QUANTUM TEACHING BERBANTUAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN PENALARAN DAN MOTIVASI SISWA SMP - Susan Meliana H; Stanley P Dewanto (Study Program of Mathematics Education of Unimed Postgraduate Program, 2009)
This paper discusses the ways in which audio visual media in Quantum teaching based learning can be used as a pedagogic means to enhance mathematics reasoning skills and to increase students’ motivation to study mathematics, based on the premise that, since audio visual media is already played a big role in many students daily life, its use can help to facilitate learning inside the mathematics classroom. Specifically, the paper reports on an intensive six-week Quantum teaching with media and audio visual’s aid at SMP BPK 1 Penabur Bandung, which sought to use audio visual media as analogous to mathematics reasoning in terms of introducing students to concepts in Data Handling material. Feedback from students indicates an appreciation of audio visual media in Quantum teaching based learning model. A high increase in average student performance (pre and post-test) is also noted.